On the “Creative Interpretation” of ICL: Causes, Ways and Limiting Methods - He-yong, Wang; Wen-hao, Liu; Yu-qin, Liu (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article examines the concept of "creative interpretation" of international criminal law (ICL), characterized as a form of "soft interpretation" driven by judicial activism. This approach aims to expand the sources of ICL in response to the international community's calls for the punishment of international crimes. The author analyzes the reasons for adopting "creative interpretation," including the lack of legal sources, the uncertainty of legal terminology, and the mixed nature of ICL. The article explores the methods used by international criminal justice institutions, such as reconstructing customary international law, resorting to natural law, and drawing analogies from national legislation. The importance of adhering to the principle of legality is emphasized, and recommendations are made to limit judicial activism: applying Article 22 of the Rome Statute to clarify the sources of ICL, affirming the priority of legal stability, developing more detailed sentencing guidelines, and introducing a "stay of proceedings" mechanism.